2014
DOI: 10.1037/a0037977
|View full text |Cite
|
Sign up to set email alerts
|

Don’t bet on it! Wagering as a measure of awareness in decision making under uncertainty.

Abstract: Can our decisions be guided by unconscious or implicit influences? According to the somatic marker hypothesis, emotion-based signals can guide our decisions in uncertain environments outside awareness. Postdecision wagering, in which participants make wagers on the outcomes of their decisions, has been recently proposed as an objective and sensitive measure of conscious content. In 5 experiments we employed variations of a classic decision-making assessment, the Iowa Gambling Task, in combination with wagering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 104 publications
(223 reference statements)
0
19
0
Order By: Relevance
“…In addition, in Study 2 we found that the majority of participants knew which option was better and had confidence in this assessment (Konstantinidis & Shanks, 2014;Maia & McClelland, 2004). Nevertheless, participantsÕ confidence in their ability to correctly identify the best option varied and this variation was predictive of the degree of choice variance they showed in the DF and policy setting tasks.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, in Study 2 we found that the majority of participants knew which option was better and had confidence in this assessment (Konstantinidis & Shanks, 2014;Maia & McClelland, 2004). Nevertheless, participantsÕ confidence in their ability to correctly identify the best option varied and this variation was predictive of the degree of choice variance they showed in the DF and policy setting tasks.…”
Section: Discussionmentioning
confidence: 77%
“…It is particularly important in sequential decisions, when subsequent choices depend on previous decisions 21,2830 . One example of such a task is a post-decision wager, in which subjects are asked to place a bet on whether their decision was correct 28,31,32 . The optimal size of the wager, the investment, depends on the degree of belief that the initial choice was correct, with a higher wager when confidence is high 32 .…”
Section: Confidence: Definition and Computationsmentioning
confidence: 99%
“…The reasons for this may be because decisions in the IOWA gambling task are predominately based on a variety of models of the environment and emotional factors (e.g., [22]), which we discuss in Section 1.3. For instance, one view is that card selection strategies are likely to change over time because people construe the IOWA gambling task as a non-stationary environment, despite the fact that it is a stationary one [27,29,30]. However, there has been considerable debate recently concerning the validity of the task and the reliability of the findings and whether much can actually be made of the learning profiles of participants in the task [27,29,30].…”
Section: Iowa Gambling Taskmentioning
confidence: 99%